The Problem of Gifted Children In Education - Dukynaitė, Rita (Acta Paedagogica Vilnensia, 2000)
The article analyses the problem of gifted children. It presents the literature review and data from various countries about the teachers’ work with gifted children and teachers’ special preparation for this work. It is pointed out that teaching programmes and textbooks have to include alternative methods to educate gifted children.